Validation of the Arabic Version of Calgary Depression Scale for Schizophrenia - Yahya Hani (3095103) (2016)
Background Patients with schizophrenia commonly show both depressive and negative symptoms that can differentially affect the prognosis and course of treatment. The Calgary Depression Scale for Schizophrenia (CDSS) was designed to distinguish between depression and negative symptoms in patients with schizophrenia. The purpose of this study is to validate an Arabic version of the CDSS among patients with schizophrenia. Methods The diagnosis of schizophrenia was confirmed using the Arabic Mini International Neuropsychiatric Interview 6 (MINI 6). A standardized translation back-translation process was adopted. One rater administered the Arabic CDSS to subjects with schizophrenia as well as to a control group who should not have any psychiatric disorder except for depression. Another rater, blinded to the results administered the already validated Arabic version of Beck Depression Inventory-II (BDI-II). Results We recruited 102 patients and 102 controls subjects. The CDSS showed good internal consistency in the active group (Cronbach’s alpha = 0.82). The Intraclass Coefficient correlations (ICC) for the inter-rater reliability (n = 21) was 0.90, p<0.05 and test-retest reliability (n = 19) was 0.85, p<0.001. When compared to the BDI-II, the cutoff score of 5 on the Arabic CDSS showed reasonable sensitivity and specificity of 72.75% and 67.95% respectively. Conclusions The psychometric properties of the Arabic version of CDSS demonstrate that it is a valid tool to assess the depressive symptoms in the Arab patients with schizophrenia. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0162304